Scumb Manifesto : Society for Cutting Up Men's Books - Gladman, Renee; Chao, Marina; Lord, Catherine; Reines, Ariana (s.l. : MACK, 2022)
"Presents a collection of collages Kurland created by cutting up and reconfiguring photobooks by male artists, as she went through the process of purging her own library of roughly 150 books by straight white men that have monopolized the photographic canon. The nature of collage--heterogeneous, pulled apart, shape shifting, disrupted, cyborg, fantasy--has long made it a feminist strategy in life and in art. Kurland's ritual is restorative and loving: each work is a reclamation of history; a dismemberment of the patriarchy; a gender inversion of the usual terms of possession; and a modest attempt at offsetting a life of income disparity. While markedly different in style, the defiant female visions pictured in these compositions are a continuation of those depicted in Kurland's earlier photographic projects 'Girl Pictures' (1997-2002) and 'Mama Babies' (2004-07). Each work in 'SCUMB' sounds an electrifying call for freedom--the freedom to create, to destroy, to imagine, and to reshape our visual and social world."--Publisher web site (viewed 2022 May 5), https://mackbooks.co.uk/products/scumb-manifesto-br-justine-kurland
(from captions) We were cuts cutting / Renee Gladman -- Cunts with the kitchen knife: notes on feminist collage and torn paper / Marina Chao -- The commonplace / Catherine Lord -- The first cut is the deepest / Ariana Reines -- SCUMB / Justine Kurland.
Some pages are on folded leaves, for example pages 39-46, 251-254.
Illustrated endpapers.
boek
Keywords: Kurland, Justine; Feminism in art; Photocollage; Photomontage; Photography, Artistic